THE DEVELOPMENT OF BUMDES (VILLAGE OWNED ENTERPRISES) SUSTAINABLE ENTREPRENEURSHIP MODEL IN INDONESIA - Ahmad Hermanto; Amilia Hasbullah; Imam Wibowo; Fredrick Tiagita Putra (Proceeding of International Conference on Entrepreneurship (IConEnt), 2022)
The establishment of BUMDes at the village government level is a strategic management of the central government to improve the village economy which is expected to have an impact on national economic growth. In practice, the existence of BUMDES currently faces the stagnant condition. Entrepreneurship has become a very important world phenomenon since couple of decades which considered as a solution to socio economic development. This paper is intended to analyze how sustainable entrepreneurship can be applied to Village-Owned Enterprises in Indonesia, and is expected to be a starting point and solution for developing sustainable BUMDes operations in Indonesia.